Germline Specific Expression of a vasa Homologue Gene in the Viviparous Fish Black Rockfish (Sebastes schlegelii) and Functional Analysis of the vasa 3′ Untranslated Region - Zhou, Li; Wang, Xueying; Du, Shuran; Wang, Yanfeng; Zhao, Haixia; Du, Tengfei; Yu, Jiachen; Wu, Lele; Song, Zongcheng; Liu, Qinghua; Li, Jun (Frontiers in Cell and Developmental Biology, 2020)
Germ cells play a key role in gonad development. As precursors, primordial germ cells (PGCs) are particularly important for germ line formation. However, the origination and migration patterns of PGCs, is poorly studied in marine fish, especially for viviparous economic species. The vasa gene has been widely used as germ cell marker to identify germline because of vasa RNA is a component of germ plasm. In this study, we described the expression pattern of Black Rockfish (Sebastes schlegelii) vasa (Ssvas) in gonadal formation and development by in situ hybridization. The results showed that Ssvas failed in localization at the cleavage furrows until late gastrula stage, when PGCs appeared, and migrated to genital ridge and formed elongated gonadal primordia at 10 days after birth. This study firstly revealed the PGCs origination and migration characteristics in viviparous marine fish. Furthermore, we microinjected chimeric mRNA containing EGFP and 3′untranslated region (3′UTR) of Ssvas into zebrafish (Danio rerio) and marine medaka (Oryzias melastigma) fertilized eggs for tracing PGCs. We found, although Sebastes schlegelii lacked early localization, similar to red seabream (Pagrus major) and marine medaka, only 3′UTR of Ssvas vasa 3′UTR of black rockfish was able to label both zebrafish and marine medaka PGCs. In comparison with other three Euteleostei species, besides some basal motifs, black rockfish had three specific motifs of M10, M12 and M19 just presented in zebrafish, which might play an important role in labeling zebrafish PGCs. These results will promote germ cell manipulation technology development and facilitate artificial reproduction regulation in aquaculture.